1979
DOI: 10.2739/kurumemedj.26.51
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Scanning Electron Microscopic Properties of Mitochondria Isolated From Rat Cardiac Muscle

Abstract: Cardiac muscle mitochondrial fraction was prepared from rat heart homogenate, according to the procedure of differential centrifugation fol lowing nagarse digestion. The biochemical intactness of isolated mitochon dria was identified by determining the oxygen consumption of respiratory chain. The field emission scanning microscope examination of the isolated mitochondria indicated that mitochondria maintained their structural in tegrity throughout the isolation procedure. The mitochondrial fraction treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In contrast with IPA experiment, administration of adriamycin caused a marked deficiency of CoQ-10 in rat heart mitochondria, and the exogenous CoQ-10 restored the CoQ-10 content in the heart mitochondria of adriamycin-treated rats to the normal level (Toyama, 1979;Ogura et al, 1979). The discrepant evidence of CoQ-10 in mitochondria is not able to explain, but the pathological mechanism of induced cardiomyopathy may be different.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In contrast with IPA experiment, administration of adriamycin caused a marked deficiency of CoQ-10 in rat heart mitochondria, and the exogenous CoQ-10 restored the CoQ-10 content in the heart mitochondria of adriamycin-treated rats to the normal level (Toyama, 1979;Ogura et al, 1979). The discrepant evidence of CoQ-10 in mitochondria is not able to explain, but the pathological mechanism of induced cardiomyopathy may be different.…”
Section: Discussionmentioning
confidence: 62%
“…Yamagami et al (1967) reported that the state 4 respiration increased in canine with infarcted heart. Sayanagi (1977), Yamauchi (1978) and Nagata (1979 in our laboratory have reported the relation of the mitochondrial respiratory disorders to the lipid peroxide formed in mitochondria exposed to ultraviolet light. The antioxidant compounds such as vitamin B2 and CoQ-10 was found to prevent the increase of lipid peroxide and restore the respiratory disorders of mitochondria.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Typical values obtained from a polarographic assay of mitochondrial respiratory responses are shown in Table 2. The morphological properties of the mitochondria prepared by this procedure were examined by transmission electron microscopy with the method of Shimada et al (Ogura et al 1979). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%